Measuring the macroeconomic determinants of agricultural price volatility: Implications for natural resource commodity prices for green recovery - Liu, Hang (Frontiers in Public Health, 2022)
By having a rapid growth, green economic recovery has been a key agenda for the globe. However, the price volatility for natural resources plays a significant role to reshape the green recovery. Therefore, the current study tries to investigate the impact of green recovery, hum,an capital index, GDP growth, forien direct investment and inflation on natural resource volatility in China over the period of 1971-2020. In order to investigate the long-term association among selected variable this study employs Autoregressive Distributive Lag (ARDL) model. In addition, the current research uses the Aikaik information (AIC) criteria for the model selections. Obtained outcomes show the significant contribution by green recovery, human capital, GDP growth, FDI and inflation increase the level of natural resource price volatility. However, to validate the results of of ARDL, this study also uses the ECM approach and validated the prior findings. On behalf of outcomes the current study implies some imperative policies to attain desired objective for green growth.